A causal sustainable product-service system using hierarchical structure with linguistic preferences in the Ecuadorian construction industry. (1st September 2019) - Tseng, Ming-Lang; Lin, Suling; Chen, Chih-Chen; Calahorrano Sarmiento, Liria Salome; Tan, Cheng Ling
Abstract: A sustainable product-service system has environmental, social and economic benefits. However, prior studies of sustainable product-service systems neglected to address the interrelationships among various aspects and criteria and did not present improvement criteria. In addition, a sustainable product-service system has an interdependent and interrelated hierarchical structure and includes measures of qualitative information. The Ecuadorian construction industry faces challenges in decreasing waste generation, improving efficiency, reducing environmental impacts, and increasing social responsibility. Hence, this study proposes a set of attributes to create a theoretical model and practical measures to assess the Ecuadorian construction industry by applying fuzzy decision-making trials with laboratory and analytical network processes to analyze the causal interrelationships among the proposed attributes in a hierarchical structure. The results provide insight into sustainable production and indicate that collaborative advantages are the most common causes of a sustainable product-service system, and employee participation, self-actualization, stakeholder relationships and empathy are the main criteria. The theoretical and industrial implications are discussed. Highlights: This study proposes a set of SPSS attributes to build a model. The attributes are with interdependence and interrelationship in a hierarchal model. The result shows sustainable production and collaborative advantage are the causal aspects. Employee participation and self-actualization are to improve the industrial performance.